BLENDED AND ONLINE LEARNING MODELS IN FOREIGN LANGUAGE EDUCATION - Orazimbetov Shingisbek,; Akkasinova Sayora, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This paper explores blended and online learning models in foreign language education, focusing on their pedagogical value in developing communicative competence and learner autonomy. It examines how digital platforms and ICT tools enhance language acquisition through interactive, flexible, and student-centered approaches. The study highlights advantages such as accessibility and engagement, as well as challenges including digital divide and learner inconsistency. It concludes that effective integration of blended learning requires balanced instructional design, teacher preparation, and technological support in modern education.